CHALLENGES IN TRANSLATION OF IDIOMATIC EXPRESSIONS AND PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Pulatova Khilola G`ayrat qizi (PEDAGOGS, 2024)
Abstract. Translation of idiomatic expressions and phraseological units poses significant challenges due to cultural nuances, linguistic structures, and contextual meanings. This article explores these challenges within the framework of English and Uzbek languages, offering comparative examples that highlight the difficulties faced by translators. It examines the role of culture in shaping idioms, the importance of context in translation, and strategies for effective translation. By analyzing these factors, this article aims to provide insights into the complexities of translating idiomatic expressions and phraseological units, ultimately fostering a deeper understanding of cross-cultural communication.